2016
DOI: 10.3390/su8111209
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics and Drivers of Farmland Changes in Panxi Mountainous Region, China

Abstract: Due to the multiple impacts of landform effects, spatial heterogeneity and land use policies, farmland dynamics in mountainous areas are complicated. This study investigated farmland dynamics based on land use data from a typical mountainous area, Panxi, in China for 1990, 2000 and 2010, discussed the relationship between altitude, slope and farmland changes and presented an analysis of the driving forces of farmland change. Our findings are as follows: (1) from 1990 to 2010, the area of converted farmland was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…The examined study region is characterized by a typical temperate monsoonal climate and experiences average temperatures between 2 • C and 6 • C [30], the rising temperatures in this area become more favorable for crop growth; the positive effects of AMT on farmland expansions in different regions might therefore be due to the fact that areas where temperature is rising tend to be more favorable for agricultural production. These positive effects of temperature on farmland expansions also appeared in existing study [16] in Panxi mountainous region, China. At the same time, the positive effects of AMT on farmland contractions might also be due to urbanization and reforestation, as these regions are also favorable for human activities and plant growth [16].…”
Section: Driving Forces Of Farmland Changessupporting
confidence: 70%
See 2 more Smart Citations
“…The examined study region is characterized by a typical temperate monsoonal climate and experiences average temperatures between 2 • C and 6 • C [30], the rising temperatures in this area become more favorable for crop growth; the positive effects of AMT on farmland expansions in different regions might therefore be due to the fact that areas where temperature is rising tend to be more favorable for agricultural production. These positive effects of temperature on farmland expansions also appeared in existing study [16] in Panxi mountainous region, China. At the same time, the positive effects of AMT on farmland contractions might also be due to urbanization and reforestation, as these regions are also favorable for human activities and plant growth [16].…”
Section: Driving Forces Of Farmland Changessupporting
confidence: 70%
“…Mountain regions tend to be more sensitive to LUCC [15] and farmland dynamics in these areas are also complicated by the multiple impacts of terrain, spatial heterogeneity, and land use policies [16]. Understanding farmland changes (both expansion and contraction referred to the cultivated surface) and their underlying driving factors is therefore important for modeling future dynamics, developing food security management strategies, and sustainable development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boncinelli et al found that proximity reduces transaction and information costs [45]. Studies in China also showed that agglomeration of population, industries and technology affected on spatial pattern of farmland [48,49]. These evidences, however, are mostly based on county level data [47], rural household level data [46], and plot level data [50].…”
Section: Research Frameworkmentioning
confidence: 99%
“…To this end, taking the implementation of this study as an example, the relationship between the main obstacles in the process of knowledge transfer (taking BIM) is established. For example, if the organization of knowledge transfer cannot adapt to the implementation of innovative technology, it will inevitably lead to the increase in the cost of knowledge transfer, the formation of organizational entities operating efficiency barriers (Peng, L., 2016).…”
Section: The Preferred Barriersmentioning
confidence: 99%